Couples, Careers, and Spatial Mobility - Lea Nassal; Marie Paul (ZBW - Leibniz Information Centre for Economics, 2021)
We examine the employment and earnings effects of long-distance moves for married couples based on a new administrative data set from Germany. Using difference-in-difference propensity score matching, we estimate the average treatment effect for moving couples while precisely accounting for pre-move employment dynamics. Our results show that men's earnings increase significantly after the move, while women suffer large losses in the first years after the move. We shed light on potential mechanisms and show that spouses' earnings response is driven by men moving to larger, higher paying establishments, whereas women move to smaller, lower paying establishments. We explore effect heterogeneity by spouses' relative earnings before the move and find evidence for gender asymmetries.phonology, Spanish, Argentina, phonemes, variation, resyllabification
Keywords: J61; J16; R23; 330; Long-distance moves; labor market careers; gender identity norms